Parental Parenting as the Foundation of Children's Character Education in the Social Media Era - Febriyanti, Ayunda; Marsofiyati, Marsofiyati; Utari, Eka Dewi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores how parenting styles shape children’s character and resilience against social media influence in the digital era. Using a descriptive qualitative approach, data were collected through interviews and observations involving 10 parents and 10 children from various backgrounds in Jakarta, Depok, Jelambar, and Bekasi. The findings show that authoritative, permissive, authoritarian, and uninvolved parenting styles affect children’s discipline, responsibility, honesty, and digital ethics differently. Strategies include supervision, access limits, open dialogue, and digital literacy. The study contributes to adaptive parenting approaches and supports the development of family-based digital literacy programs. Collaboration among parents, educators, and stakeholders is essential to foster a safe and supportive digital environment for children’s character development.